Design approach to blended learning in teaching EFL for Indonesian university students - Nila Kurnia Sari (Universitas Negeri Yogyakarta, 2020)
With the rapidly increasing involvement of technology in the teaching and learning process in higher education, lecturers are constantly on the lookout for better ways to integrate technology into their classes. Blended learning emerged in 2000 and has been one of the most popular approaches to teaching EFL. Despite having been around for years, not many people fully understand the principle behind it and how to design an effective blended course. Such is the case in most higher education institutions in Indonesia. This article reports on the result of a survey-based research in which the aim was to investigate how EFL lecturers in Yogyakarta State University, Indonesia design their blended courses. As many as 9 lecturers were involved as respondents in an online survey, an interview, and documents inspection. The data from the survey were then analyzed using two major theories of blended learning design approach by Lai, M., Lam, K. M., Lim, C. P. (2016) and Alammary, Sheard, and Carbone (2014). The findings revealed that EFL lecturers designed their blended learning based on the principle of extension by Lai, M., Lam, K. M., Lim, C. P. (2016) and the low-impact model Alammary, Sheard, and Carbone (2014) was preferred to the other models.